ENTREPRENEURIAL SELF-EFFICACY AND CREATIVE CAPACITY AT THE NATIONAL INTERCULTURAL UNIVERSITY OF THE AMAZON - Oseda Gago, Dulio (2019)
ABSTRACT The objective of this study is to identify the relationship between the entrepreneurial self-efficacy variable and the creative capacity of the students of the engineering and environmental sciences courses of the UNIA. The investigation according to the nature was the type of application, the level of correlation, and the simple descriptive - correlational design, with a probabilistic and stratified type sampling conformed by 294 students. The instruments prior to its application were reliably and validated in a timely manner. The main conclusion is that there is a direct correlation (rho = 0.956) and highly significant (p-value: 0.000) between the variable entrepreneurial self-efficacy and creative capacity in students of engineering careers and environmental sciences of the UNIA region Ucayali. KEYWORDS: Entrepreneurial self-efficacy, innovation and creative capacity.